Prohibition of the use of evidence in the case of unlawfully obtained evidence? - Schneider, Anne (European Integration Studies, 2023)
The question of whether evidence that was obtained unlawfully can be admitted as evidence is discussed in any criminal justice system. This paper examines the solutions that can be found in EU secondary and primary law and in the case-law of the Court of Justice of the European Union. It reveals that different area of EU law use different approaches, which can be explained by the underlying rationales.